FACTORS OF DEVELOPMENT PROCESSES OF SOCIO-POLITICAL BASES OF NGOS IN NEW UZBEKISTAN - Masharipov Ikramjon Batirovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article reveals the author’s formed analytical opinions about the development strategy of New Uzbekistan, the main unit of society is a person who is free from political dependence and able to use his rights; NGOs, public organizations and actions formed based on the need to express various interests and implement them; non-state socio-economic relations and institutions (private property, labor, entrepreneurship, etc.); producers independent of the state (private firms, etc.); voter associations, various clubs and circles; municipal, i.e. self-governing bodies; non-state sector of education and training; non-state mass media; various lobby organizations that connect civil society with the state around political parties, legislative and representative bodies; family; Based on the activities of entrepreneurs, farmers’ organizations, trade unions, consumer associations, scientific, cultural and religious organizations, sports societies, etc.